NASIONALISME DALAM REPUBLIK JANGKRIK KARYA ABEL TASMAN - H, Rosman (Jurnal Ilmu Budaya, 2012)
This writing entitles "Nationalism in Republic Jangkrik Written by Abel Tasman". This writing proves that the power of Raja Rimba is no longer hegemonic. The establishment of Republic Jangkrik is the refusal of Raja Rimba's domination. The establishment of Republic Jangkrik is the agreement of Jangkrik society to live in one state and the denial of the state of raja Rimba, it means the Jangkrik society refuses to be under raja Rimba's control and it shows their solidarity among Jangkrik Society.